The Greek Influence on Primitive Irish Literature - Sainero, Rámon (ABEI Journal, 2003)
There are surprising similarities between some Greek and Irish tales. The aim of this paper is to attempt a brief explanation of these similarities, or influences, firstly by studying the tales that appear in the Irish manuscripts and then the tales that appear in the works of Classical Greek writers such as Homer, Herodotus or Hesiod. We have chosen the following tales to demonstrate these similarities: “The prophecy of Paris Prince of Troy” and the Irish epic Tain Bo Cuailnge. “The prophecy of Paris Prince of Troy” and the tale of “The prophecy of Deirdre”. “The apple of disagreement” or “The Judgment of Paris” and the tale of “Bricriu’s Feast”. “Leda and the Swan” and the tale of “Aonghus and the Swan”. A study of Homer’s Iliade reveals several important similarities between Helene and Deirdre, Cuchulain and Aquiles, Hector and Ferdius. The manner of presentation of the challenge for the bull of Conchubar King of Ulster, in the Tain Bo Cuailnge, is echoed in the primitive Greek tale of the challenge for the bull of Paris Prince of Troy and Briciu’s Feast, another tale in the Ulster Cycle, is the development of the tale of “The Judgment of Paris”. It is my belief that we should not talk only of similitude, but also of relations. The theory that the origins of these primitive Irish people is somehow connected with the primitive culture of the Middle East; Greece, Thracia and the Black Sea, is supported in the primitive literature of the people who inhabited those territories. I put forward the possibility that these primitive Greek tales known by the Irish scribers form one whole, single Irish identity, combining the Greek and Irish materials.